ANALISIS PENGARUH DISIPLIN KERJA, KOMITMEN KERJA DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA YAYASAN PERGURUAN DR. WAHIDIN SUDIROHUSODO MEDAN - Sinaga, Triana Melinda (Sekolah Tinggi Manajemen Bisnis (STMB) MultiSmart, 2020)
The research in this thesis is motivated by the weakening of work performance of employees. This can be seen, among others, that there are still many employees who have not been trusted by superiors, the enthusiasm of employees in completing tasks given is low, the openness of employees in expressing opinions to superiors is low, lack of employee discipline in completing routine tasks. Work discipline factors, commitment and work environment, are the focus of this study, because these factors can affect employee performance. The purpose of this study was to find out, analyze and assess the effect of work discipline, commitment and work environment on employee work performance at the National College Foundation, dr. Wahidin Sudirohusodo Medan. The research approach used is descriptive and quantitative with the type of survey research. The population in this study was 76 people. While the sample of this study is a saturated sample where the sample is the entire population. This study, called population research using the census method The results of the study show (1) There is a positive and significant influence between work discipline on employee work performance at the National College Foundation Dr. Wahidin Sudirohusodo Medan. (2) There is a positive and significant influence between commitment to employee work performance at the National College Foundation, dr. Wahidin Sudirohusodo Medan. (3) There is a positive and significant influence between the work environment on employee performance at the National College Foundation, dr. Wahidin Sudirohusodo Medan. (4) There is a positive and significant influence between work discipline, commitment and work environment on employee work performance at the National College Foundation Dr. Wahidin Sudirohusodo Medan with a coefficient of determination 88.30% means that work discipline, commitment and work environment affect the work performance of employees at the National College Foundation Dr. Wahidin Sudirohusodo Medan, while 44,1% was influenced by other factors not discussed in this study. Keywords: Work Discipline, Work Commitment, Work Environment, Work Performance